2022
DOI: 10.1364/oe.455796
|View full text |Cite
|
Sign up to set email alerts
|

Flexible transparent CMUT arrays for photoacoustic tomography

Abstract: This paper reports the fabrication and characterization of the first flexible transparent capacitive micromachined ultrasound transducer (CMUT) array for through-illumination photoacoustic tomography. Fabricated based on an adhesive wafer bonding technique and a PDMS backfill approach, the array has a maximum transparency of 67% in visible light range and can be bent to a radius of curvature of less than 5 mm without the structural layers being damaged. With a center frequency of 3.5 MHz, 80% fractional bandwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Lead magnesium niobate (PMN) with low lead titanate (PT) doping is a electrostrictive material that is naturally unpolarized at around room temperature and becomes polarized by applying a DC bias voltage (PMN38, TRS Technology). These materials can also be made transparent/translucent when polished on both sides that potentially can be used in through-illumination photoacoustic applications [26], [27]. Capacitive micromachined ultrasound transducer (CMUT) is another bias-sensitive transducer that uses electrostatic forces between two clamped plates to generate acoustics which some of their applications in TOBE configurations have been demonstrated recently [8].…”
Section: Experimental Methods a Bias-sensitive Ultrasound Transducer ...mentioning
confidence: 99%
“…Lead magnesium niobate (PMN) with low lead titanate (PT) doping is a electrostrictive material that is naturally unpolarized at around room temperature and becomes polarized by applying a DC bias voltage (PMN38, TRS Technology). These materials can also be made transparent/translucent when polished on both sides that potentially can be used in through-illumination photoacoustic applications [26], [27]. Capacitive micromachined ultrasound transducer (CMUT) is another bias-sensitive transducer that uses electrostatic forces between two clamped plates to generate acoustics which some of their applications in TOBE configurations have been demonstrated recently [8].…”
Section: Experimental Methods a Bias-sensitive Ultrasound Transducer ...mentioning
confidence: 99%
“…To quantify the device spatial resolutions using the wide-beam compounding strategy, we measured full widths at half maximum from the point spread function curves 28 extracted from the images (Fig. 2a , third and fourth columns and the bottom row and Supplementary Fig.…”
Section: Imaging Strategies and Characterizationsmentioning
confidence: 99%
“…Mahyar et al proposed a flexible transparent CMUT array with a center frequency of 3.5 MHz, an 80% fractional bandwidth and a noise equivalent pressure (NEP) of 62 . The flexible CMUT array was fabricated based on an adhesive bonding technique with benzocyclobutene (BCB) as both the adhesive and sidewall layers, ITO as the electrodes, silicon nitride as the membrane, and PDMS as the flexible backing layers [ 15 ]. The fabrication processes, optical microscopy images, photographs, NEP and frequency spectrum of the transparent flexible CMUT array are shown in Figure 6 c.…”
Section: Flexible Us Transducer Designs For Imaging Applicationsmentioning
confidence: 99%
“…Mahyar et al bonded a 64-element CMUT array to a flexible PCB to detect PA signals, as shown in Figure 9 b. The PAI system with a flexible CMUT array showed an SNR of 46 dB with an axial and lateral resolution of 382 μm and 293 μm, respectively [ 15 ]. Liu et al used a single-element US transducer with a 6.7 MHz center frequency and 86.3% −3 dB fractional bandwidth in a PAI system, as shown in Figure 9 c [ 26 ].…”
Section: Practical Imaging Applications With Flexible Us Transducersmentioning
confidence: 99%
See 1 more Smart Citation